Efforts to Improve Creative Thinking Skills and Communication Skills Through the Application of Project Based Learning Models - Annur Miftahul Jannah; Yennita; Azizahwati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to improve students' creative thinking and written communication skills through the application of project-based learning methods (PjBL) on alternative energy materials. The study was conducted at MAN 2 Pekanbaru City, class X.5, involving 36 students. This classroom action research was carried out in two cycles, each consisting of planning, implementation, evaluation, and reflection. The instruments used included teaching modules, student worksheets (LKPD), observation sheets, and test questions. The results showed a significant increase in students' creative thinking skills. In cycle I, the fluency indicator reached 76%, flexibility 73%, originality 36%, and elaboration 63%. In cycle II, each indicator increased to 78%, 87%, 76%, and 87%. Written communication skills also increased, with the dimension of changing the form of data presentation increasing from 72% in cycle I to 78% in cycle II, and the accuracy of using tables and graphs from 79% to 87%. The PjBL method provides opportunities for students to be actively involved in learning through project activities that encourage creative thinking and effective communication. The results of this study indicate that the PjBL method is effective in improving students' cognitive and communication skills, although it requires further adjustments related to classroom management.